Decision-analytic modeling to evaluate the long-term effectiveness and cost-effectiveness of HPV-DNA testing in primary cervical cancer screening in Germany - Sroczynski, Gaby (German Medical Science GMS Publishing House, 2010)
BACKGROUND: Persistent infections with high-risk types of human papillomavirus (HPV) are associated with the development of cervical neoplasia. Compared to cytology HPV testing is more sensitive in detecting high-grade cervical cancer precursors, but with lower specificity. HPV based primary screening for cervical cancer is currently discussed in Germany. Decisions should be based on a systematic evaluation of the long-term effectiveness and cost-effectiveness of HPV based primary screening. RESEARCH QUESTIONS: What is the long-term clinical effectiveness (reduction in lifetime risk of cervical cancer and death due to cervical cancer, life years gained) of HPV testing and what is the cost-effectiveness in Euro per life year gained (LYG) of including HPV testing in primary cervical cancer screening in the German health care context? How can the screening program be improved with respect to test combination, age at start and end of screening and screening interval and which recommendations should be made for the German health care context? METHODS: A previously published and validated decision-analytic model for the German health care context was extended and adapted to the natural history of HPV infection and cervical cancer in order to evaluate different screening strategies that differ by screening interval, and tests, including cytology alone, HPV testing alone or in combination with cytology, and HPV testing with cytology triage for HPV-positive women. German clinical, epidemiological and economic data were used. In the absence of individual data, screening adherence was modelled independently from screening history. Test accuracy data were retrieved from international meta-analyses. Predicted outcomes included reduction in lifetime-risk for cervical cancer cases and deaths, life expectancy, lifetime costs, and discounted incremental cost-effectiveness ratios (ICER). The perspective of the third party payer and 3% annual discount rate were adopted. Extensive sensitivity analyses were performed in order to evaluate the robustness of results and identify areas of future research. RESULTS: In the base case analysis screening resulted in a 53% to 97% risk reduction for cervical cancer with a discounted ICER between 2,600 Euro/LYG (cytology alone every five years) and 155,500 Euro/LYG (Annual cytology age 20 to 29 years, and annual HPV age 30 years and older). Annual cytology, the current recommended screening strategy in Germany, was dominated. In sensitivity analyses variation in the relative increase in the sensitivity of HPV testing as compared to cytology, HPV test costs, screening adherence, HPV incidence, and annual discount rate influenced the ICER results. Variation in the screening start age also influenced the ICER. All cytology strategies were dominated by HPV screening strategies, when relative sensitivity increase by HPV testing compared to cytology was higher (scenario analysis with data for test accuracy from German studies). HPV testing every one, two or three years was more effective than annual cytology. With increased screening adherence a longer screening interval and with low screening adherence a shorter interval would be more cost-effective. With a reduction in HPV incidence of more than 70% triennial HPV screening in women aged 30 years and older (and biennial Pap screening in women aged 20 to 29 years) is cost-effective. The discounted ICER increases with increasing annual discount rate. Increasing screening start age to 25 years had no relevant loss in effectiveness but resulted in lower costs. An optimal strategy may be biennial HPV testing age 30 years and older with biennial cytology at age 25 to 29 years (ICER of 23,400 Euro/LYG). CONCLUSIONS: Based on these results, HPV-based cervical cancer screening is more effective than cytology and could be cost-effective if performed at intervals of two years or greater. Increasing the age at screening start to 25 years causes no relevant loss in effectiveness but saves resources. In the German context an optimal screening strategy could be biennial HPV testing at age 30 years and older with biennial cytology at the age of 25 to 29 years. An extension to a three-yearly screening interval requires substantially improved screening adherence or a higher relative increase in the sensitivity of HPV testing as compared to cytology. The implementation of an organised screening program for quality-controlled introduction of HPV-screening and -vaccination with continued systematic outcome evaluation is recommended.